A new similarity criterion and design method for wind tunnel model tests of floating offshore wind turbines. (1st February 2023) - Wang, Xinbao; Cai, Chang; Zhou, Teng; Yang, Yingjian; Chen, Yewen; Wang, Tengyuan; Hou, Chengyu; Zhou, Shuni; Li, Qing'an
Highlights: A new similarity criterion is proposed for FOWT's wind tunnel model tests. The mapping of the optimal TSR between the model and the prototype is considered. The similarity of the changing rate of the relative TSR is also considered. Hysteresis effects are captured with respect to the relative TSR under surge motions. Dynamic aerodynamic performances of the prototype can be reflected more accurately. Abstract: Floating offshore wind turbines (FOWTs) have received strong attention in recent years, and numerous experimental studies have been conducted on them. However, the small-scaled wind turbine models designed by the criterion of traditional thrust coefficient similarity are unable to obtain similar power coefficients with the prototype, and they are not able to reflect the expected dynamic aerodynamics induced by the platform motions. To this end, this paper presents a new criterion for wind tunnel model tests based on the mapping of the optimal tip speed ratio (TSR) and the similarity of the changing rate of the relative TSR. The National Renewable Energy Laboratory's offshore 5-MW wind turbine is selected as the prototype wind turbine. The blade of the model wind turbine is generated by NACA 4412 airfoil, and the chord and twist are optimized by the genetic algorithm. The objective is to keep the thrust and power coefficients of the model wind turbine around the optimal TSR consistent with that of the prototype through a linear mapping relationship. Dynamic simulations with the Unsteady Blade-Element Momentum method are performed to verify the new similarity criterion at different surge frequencies. Compared with those of the model wind turbine designed by the traditional method, fluctuations of the mapped thrust and power coefficients of the new model are in better agreement with the prototype. Hysteresis effects with respect to the relative TSR are newly captured, and loops of the new model are also closer to that of the prototype. This paper provides a more reasonable criterion for wind tunnel model tests of FOWTs, and the dynamic aerodynamics of the prototype can be reflected more accurately compared with the traditional method, which is important for the performance evaluation and optimization design of large-scale FOWTs.